The effectiveness of a training program in the development of emotional intelligence of science and mathematics teachers of in the Sultanate of Oman - AL Ghafri, Hamed Hamood; Aldhafri, Said Sulaiman; Al kharusi, Hussain Ali; Al Busaidi, Saleh Salim; Ambusaidi, Abdullah Khamis; Alrajhi, Marwa Nasser; Al-Kharusi, Bader Hamood; Al-Hosnia, Khoula bint zaher (Journal of Educational and Psychological Sciences, 2020)
The study aimed at preparing a training program using Daniel Goleman's theory, and evaluating its effectiveness in improving the emotional intelligence of 21 level 2 math and science teachers in Oman by measuring their reaction towards the program and their learning (knowledge, skills, confidence in applying the acquired skills). The study also aims at recognizing the program's effectiveness in developing the emotional intelligence in the targeted group through pre and post tests on emotional intelligence developed by Schutt et. al (1998) which was used as a semi- experimental, an experimental design of one group.The program is designed to be offered in 10 days, with a total of 50 hours, 5 hours daily, and includes 10 training indicating units. Study findings reveal a positive reaction with the study sample towards the program by an average of 4.44. There was also an improvement in the learning level after the program, as knowledge and skills improved from an average of 1,90 to 2,95. Besides, trust in acquiring the skills developed from 2,10 to 2,86.Furthermore, results reveal statistical differences of the emotional intelligence measurement at (,001) among the averages of the study sample of (3,85) pre-test and (4,16) post-test, which proves the effectiveness of the program in developing emotional intelligence. Finally, the study resulted on a high impact of (1,123) using Cohen's formula standards in calculating the impact of the program as an Independent Variable in the emotional intelligence as a Dependent. Variable.
Keywords: training program; emotional intelligence; teachers; Sultanate of Oman